CROWN OF SNAKES: EURIPIDES, BACCHAE 101-2. (1st June 2016) - Lane, Nicholas
Abstract : ἔτεκεν δ᾽, ἁνίκα Μοῖραι τέλεϲαν, ταυρόκερων θεὸν 100 ϲτεφάνωϲέν τε δρακόντων ϲτεφάνοιϲ, ἔνθεν ἄγραν θηρότροφον μαι- νάδεϲ ἀμφιβάλλονται πλοκάμοιϲ. 102-3 θηρότροφον praeeunte Musgrave (-τρόφον) Allen : -τρόφοι ‹L›P The subject of ἔτεκεν (99) and ϲτεφάνωϲεν (101) is Zeus (95). If the text is right, Zeus gave birth to Dionysus, and Zeus then crowned him with snakes. This note argues that the text is corrupt because (i) vase painting shows Dionysus born already crowned, and (ii) the notion that Zeus should crown anyone is quite exceptional. I conclude that in 101 Euripides probably wrote ϲτεφανωθέντα, not ϲτεφάνωϲέν τε.